If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying e + 5(e + 2) = 46 Reorder the terms: e + 5(2 + e) = 46 e + (2 * 5 + e * 5) = 46 e + (10 + 5e) = 46 Reorder the terms: 10 + e + 5e = 46 Combine like terms: e + 5e = 6e 10 + 6e = 46 Solving 10 + 6e = 46 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 6e = 46 + -10 Combine like terms: 10 + -10 = 0 0 + 6e = 46 + -10 6e = 46 + -10 Combine like terms: 46 + -10 = 36 6e = 36 Divide each side by '6'. e = 6 Simplifying e = 6
| 9c-7=7c+5 | | x^2+170x-6000=0 | | .5(4-x)=9 | | 20-40=28/3(h-6) | | 108=x+(x-2) | | 20-28=44/13(18-4) | | 1/5(x+10)=6 | | 5X-10Y=13 | | 4x+14=62-2 | | 20-28=44/13(h-4) | | (4x^3-8x^2+1)-(4x^3-1)= | | p-40=28/3(18-6) | | p-28=44/13(18-4) | | 0.8x-0.7x+0.4x=4 | | 0.8x-0.7x+0.4w=4 | | f(x)=x^2+6x+5 | | 2x*4=4(x+3) | | 2(n+4)=96+2(2n+2n) | | 14x^2-32y= | | (1/12)*x=(1/4)*x | | v=12u | | 25x^2=60x-26 | | 12(x+9)=96 | | (x+2)/2=(x-1)/4 | | z/5-6=41/3 | | 3z-5z=18 | | y-5y+4=0 | | 3x-3y=-15 | | 7x-12=3x+8 | | 10x-10=6x+5 | | z/5-4=15/8 | | 4x+29=7x+4 |